(untitled) (Research, Society and Development, 2021)
Coffee is one of the most commercialized beverages in the world, and the high consumption of this beverage is due to the compounds of this fruit, such as polyphenols, caffeine and chlorogenic acids, which have antimutagenic and antioxidant properties. For this reason, the objective of this work is to measure and comparatively evaluate physical-chemical parameters and the presence of bioactive compounds between caffeinated and decaffeinated coffees, in order to inform whether the loss of compounds in decaffeinated roasted coffees is significant to the point of nullifying its properties or hinder the obtainment of them. For this purpose, 12 samples of caffeinated and decaffeinated coffees were collected in 3 supermarkets in the city of Belém-PA, which were subjected to tests of pH, refractive index, moisture, acidity, ascorbic acid, polyphenols and flavonoids. The physicochemical results were expressed as median, quartiles, minimum and maximum and antioxidants as mean ± standard deviation, namely: pH 5 and pH 4.87; °Brix 1.335 and 1.334; humidity 5.44% and 5.68%; acidity 10ml NaOH/ml and 11.2ml; 2.10% and 1.99% ascorbic acid, 213.32 mgEAG/g and 208.22 mgEAG/g polyphenols; 23.8mg/100g and 17.6mg/100g of anthocyanins; 9.79mg/100g and 9.73mg/100g and yellow flavonoids for caffeinated and decaffeinated coffees, respectively. In conclusion, decaffeinated coffees have physicochemical parameters higher to caffeinated ones and lower in antioxidant levels. Therefore, the consumer will not be harmed choosing anyone of them.